Cas9-targeted-based long-read sequencing for genetic screening of RPE65 locus - Rodilla, Cristina; Núñez-Moreno, Gonzalo; Benitez, Yolanda; Romero, Raquel; Fernández-Caballero, Lidia; Mínguez, Pablo; Corton, Marta; Ayuso, Carmen (Frontiers in Genetics, 2024)
Introduction Long-read sequencing (LRS) enables accurate structural variant detection and variant phasing. When a molecular diagnosis is suspected, target enrichment can reduce the cost and duration of sequencing. Methods LRS was conducted in five inherited retinal dystrophy (IRD) patients harboring a monoallelic variant in RPE65 that remained uncharacterized after clinical exome sequencing (CES). CRISPR-Cas9 guide RNA probes were designed to target a 31 kb region, including the entire RPE65 locus. The DNA was sequenced on a MinION platform. Short-read ×30 whole-genome sequencing (WGS) was performed for five patients to validate nanopore results. Results The nanopore sequencing process yielded a median of 271 reads within the targeted region, with a mean depth of 109 and a median read size of 8 kb. All variants identified by CES have been detected using this approach, and no additional RPE65 gene causative variants were found. Nanopore variant detection demonstrated performance akin to short-read WGS at similar coverage levels, although exhibiting increased false positive calls at lower coverage. Discussion In this study, we explore the advantages of using a targeted approach together with long-read sequencing to identify variants associated with IRD. The results underscore the utility of targeted long reads for characterizing patients affected by rare diseases when first-tier diagnostic tests are non-conclusive.